Pengembangan Media Pembelajaran Perkalian Pecahan Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas IV: Matematika, Media, Pembelajaran, Pengembangan - Norhalizah; Istiyati Mahmudah (IAI DARUL ULUM KANDANGAN, 2025)
This research develops interactive multimedia-based learning media for multiplying fractions for grade 4 students at SDIT Al Ghazali Palangka Raya. The goal is to improve students' problem solving abilities. This research uses the ADDIE development model, and involves interviews with teachers to get input in the media development process. The research results show that the learning media developed is effective in improving the problem solving abilities of 4th grade elementary school students.